A study to assess the gynecological problems among adolescent girls attending gynecology out patient department in secondary care hospital in North East India - Joshi, Reetika; Duomai, Veino Kuveio (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Adolescence is a period of transition between childhood and adulthood. It is marked by enormous biological, physical and psychological changes. The young girls are embarrassed to discuss their gynecolgical problems and are hesitant to seek medical help, however their problems need to be identified and addressed. This study identifies the major health problems faced by adolescent girls. Methods: This research study was conducted at Baptist Christian hospital, Assam from Oct 2019 to Mar 2020. A total of 61 adolescent girls in the age group of 10 to 19 years attending gynecology out patient department of Baptist Christian hospital, Assam were included in this study. Results: Most of the girls who attended the OPD were between 17 to 19 years of age (54%). Maximum number (75%) of girls attain menarche at the mean age of 12.6 years. 55.7% of girls presented with menstrual disorders and the most common menstrual disorder was found to be menorrhagia (32%), followed by oligomenorrhea (29%). Conclusions: This study gives out that young girls must be taught to take care of their body and they must be made aware of their bodily changes during growing up years. Health education regarding menstrual hygiene, menstrual problems and reproductive health should be imparted to them.